ANTIOXIDANT ACTIVITY OF TYROSINASE ENZYME IN DRY RED WINES - Irgasheva, Gulmira; Saida, Xakimova; Malika, Utkirova (Journal of Higher Education and Academic Advancement, 2025)
Objective: This research aims to investigate antioxidants and their role in protecting wine from oxidation processes. Specifically, it focuses on understanding the oxidation of wines, such as dry red wines (Cabernet), and developing the theoretical foundation for the preparation of oxidized wines. Additionally, the study aims to improve new technologies for the production of finished wine products with high added value, based on the deep processing of local raw materials. Method: The research involves the analysis of various antioxidants and their application to prevent oxidation in wine. Experimental methods are used to study the oxidation processes in different wine varieties, particularly Cabernet. Techniques for deep processing of local raw materials are also explored to enhance the production of wine with higher added value. Result: The study identifies effective antioxidants that can protect wines from oxidation, particularly in the case of dry red wines like Cabernet. The research also provides a comprehensive theoretical framework for understanding and managing oxidation in wines. Additionally, new technologies for producing wine with higher added value have been developed, utilizing local raw materials. Novelty: The novelty of this research lies in its approach to combining antioxidant protection with the improvement of wine production technologies. The focus on dry red wines, such as Cabernet, and the deep processing of local raw materials for added value is a unique contribution to the field. The study provides innovative insights into the development of wine products with enhanced quality and market value.